2016
DOI: 10.1095/biolreprod.116.140400
|View full text |Cite
|
Sign up to set email alerts
|

The Behavior and Acrosomal Status of Mouse Spermatozoa In Vitro, and Within the Oviduct During Fertilization after Natural Mating

Abstract: Although 90%-100% of mouse oocytes can be fertilized in vitro with capacitated spermatozoa within 1 h after insemination, oocytes within the oviduct are fertilized one by one over a period of several hours. In vitro experiments showed that both acrosome-intact and acrosome-reacted spermatozoa entered the cumulus oophorus, but that acrosome-reacted spermatozoa reached the surface of oocytes more readily than acrosome-intact spermatozoa. During the period of fertilization within the oviduct, acrosome-reacted spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
65
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 62 publications
7
65
0
Order By: Relevance
“…The number of spermatozoa with NPR2-positive staining was further increased after treatment with NPPC, suggesting that only the spermatozoa with functional NPR2 are attracted by NPPC. This is consistent with recent studies that only a few spermatozoa migrate from the isthmus to the ampulla during the progression of fertilization616263. Thus, the capacitated spermatozoa show attraction by exposing the functional receptor NPR2, and travel from the isthmus of the oviduct to the ampulla during ovulation.…”
Section: Discussionsupporting
confidence: 92%
“…The number of spermatozoa with NPR2-positive staining was further increased after treatment with NPPC, suggesting that only the spermatozoa with functional NPR2 are attracted by NPPC. This is consistent with recent studies that only a few spermatozoa migrate from the isthmus to the ampulla during the progression of fertilization616263. Thus, the capacitated spermatozoa show attraction by exposing the functional receptor NPR2, and travel from the isthmus of the oviduct to the ampulla during ovulation.…”
Section: Discussionsupporting
confidence: 92%
“…For many years, the acrosome reaction was postulated to occur upon sperm interaction with the zona pellucida of ovulated eggs (Buffone, Hirohashi, & Gerton, ; Hirohashi, ). Yet, recent studies reported that acrosomal exocytosis is triggered before reaching the ampulla, where fertilization occurs in the mouse (Hino et al, ; Muro et al, ; Spina et al, ). Our current study suggests that spermatozoa require an intact acrosome to sense a chemical guidance cue, leading to the hypotheses that chemotaxis precedes acrosomal exocytosis and that both processes sequentially occur en route to the egg.…”
Section: Discussionmentioning
confidence: 99%
“…Spermatozoa must exocytose its acrosome in order to bind to and fuse with the egg plasma membrane (Cuasnicú, Da Ros, Weigel Muñoz, & Cohen, ). Most fertilizing mouse spermatozoa complete this acrosome reaction before reaching the zona pellucida (Jin et al, ), probably while travelling through the upper isthmus (Hino et al, ; Muro et al, ; Spina et al, ). Therefore, an intriguing question is whether or not the responsiveness to a chemoattractant can change depending on acrosome's integrity.…”
Section: Introductionmentioning
confidence: 99%
“…The release of these hydrolytic enzymes is thought to facilitate the sperm penetration of the cumulus oocyte complex [29]. However, recent publications have shown that mouse spermatozoa that reach the fertilization site have already undergone AE [30] and the same seems to occur in cattle [31][32][33]. The AE is a calcium-dependent exocytotic event [28] that can be artificially induced using calcium ionophores, such as ionomycin and A23187, and also with physiological molecules, such as progesterone or glycoproteins from the zona pellucida of some species [34,35].…”
Section: Introductionmentioning
confidence: 99%